Severe menopausal symptoms in mid-aged Latin American women can be related to their indigenous ethnic component (2011)
Background Latin American women present more severe menopausal symptoms when compared to those from other regions of the world. Since this population is an ethnic blend of Caucasian and indigenous people, we sought to test the hypothesis that severe menopausal symptoms in Latin American women are associated with an indigenous origin. Objective To assess menopausal symptoms among two specific indigenous Latin American populations. Method A total of 573 natural postmenopausal indigenous women aged 45–59 years (288 Quechua (Peru) and 285 Zenu´ (Colombia)) living in isolated communities were surveyed with a general questionnaire and the Menopause Rating Scale (MRS). Results The total MRS score was significantly higher among Quechua women as compared to Zenu´ ones (22.7+5.7 vs. 14.7+2.5, p50.0001); both figures were higher than those described for Hispanic or European populations. Quechua women presented more intense somatic and psychological symptoms as compared to Zenu´ (8.8+2.3 vs. 5.3+1.8; and 7.8+2.4 vs. 3.2+1.7, p50.0001); however, both indigenous groups presented similar intense urogenital symptoms (6.1+1.6 vs. 6.2+1.4, not significant). These differences persisted after adjusting for age, years since menopause onset and parity. The percentage of women presenting severe somatic and psychological symptoms significantly increased with aging among Quechua. This was not the case for Zenu´ women. More than 90% of indigenous women (Quechua and Zenu´) at all age intervals presented severe urogenital scores, a percentage that is much higher than that described in the world literature. Conclusion Severe menopausal symptoms found among Latin American women could be the result of their indigenous ethnic origin; the urogenital domain is the most affected.